DEVELOPMENT DYNAMICS OF UNIVERSITY COOPERATION AND CIVIL SOCIETY ORGANIZATION IN PARTNERSHIP PROGRAM OF UNIVERSITY-SOCIETY (Gender Equality Initiation in Cambaya’s Community Activity) - Masse, Ambo; Syam, Jumriah (Universitas Islam Negeri Alauddin Makassar, 2014)
This paper aims to describe the program implementation model conducted by Working Group IV, one of the Working Groups formed in SILE project of Makassar by considering the gender equality initiation of Cambaya’s community activities. One of the important results in ABCD approach is the establishment of Core Group derived from Cambaya own society. The group then organizes the society in advocating policies of institutions related to the public participation in public service. The entire processes of the activity stages are still controlled together by considering the aspect of gender equality. Generally, the practice of gender equality in the society has developed the awareness of respect and equality patterns in the societies’ daily activities and public services in the environment of Cambaya sub-district. The group was very actively in conducting the society mediation and mentoring related to the woman empowerment, the issues of domestic violence, the issues of child protection, and very actively help to mediate with the law enforcement officials when there were community members who had problems with the law.